An assessment of school feeding programme - pilot phase and its relationship with enrolment attendance retention and the local agricultural production in Nampula province in Mozambique - Kiamba, Josephine M. (University of Pretoria, 2018)
Background: In developing countries hunger, poverty and malnutrition are constraint to learning. Unfortunately, the primary school children are the most affected group due to their vulnerability. Implementation of school feeding programmes can improve both the welfare of school children and the livelihood of local smallholder farmers. Aim: This study assessed the role of the Mozambique National School Feeding Programme on enrolment, retention, and attendance of learners, and its possible role in local agriculture, in Nampula Province, 2013-2015. Methods: Mixed method research was applied, which is a combination of qualitative and quantitative approaches. Secondary data was obtained on learner enrolments, attendance and dropouts for eight purposively selected schools from school and Provincial Directorate of Education records. The opinions of learners, teachers, and principals were surveyed using semi-structured interviews. Focus group discussions were held with parents’ committee members and farmers. Chi square tests and logistic regression models were used to predict the likelihood of enrolment and retention of learners in schools that either introduced or did not introduce school feeding programs; the Mann-Whitney test was used to compare the median number of days missed at school. Results: After the national school feeding programme was introduced in 2014, enrolments increased in the four schools with feeding schemes (2014: Chi(6df)35.4279, p<.001, 2015: Chi(6df)32.7172, p<.001). In 2013, all eight schools had similar retention rates (Chi(6df)7.7302, p<.259). However, after the introduction of school feeding programme, learner retention rates in the schools with feeding schemes were significantly higher (Chi(6df) 222.2180, p<.001) and 2015 Chi(6df)32.6221, p<.001). Both univariate and multivariate logistic regression modelling confirmed increased enrolment and retention following the introduction of school feeding. Concerning attendance, the Mann-Whitney test showed that in 2013, before to the introduction of school feeding programme, there was no significant difference between schools with school feeding programme and schools without p= 0.8879. However, after the introduction of the school feeding programme, a statistically significant difference was found between the median number of absent days between the two groups of schools (p= <0. 001). A balanced menu was developed, but because school feeding was only introduced in 2014, there was no time for farmers to cultivate the required foods. However, the results obtained from interviews with key informants revealed that most products used in the NSFP can be grown locally. Focus group discussions indicated that all stakeholders were in favour of the scheme. Conclusion: The role of school feeding programmes on educational outcomes for children is difficult to measure because of external variables such as the quality of education received, teacher subject knowledge or availability of teachers and access to resources. However, the assessment compensated for these variables as much as possible by triangulating the results of all three methodologies. The results of the study indicate that the introduction of a school feeding programme in Nampula Province, Mozambique, appears to have a positive influence on the increased enrolment, attendance, and retention of primary school learners. Schools without school feeding programs failed to retain learners. Furthermore, it seems that most of the foodstuffs included in the menu could be grown locally in future. It is recommended that the role of local agriculture in the Mozambique National School Feeding Programme should be the subject of further research, especially as seasonality needs to be considered.